The effects of human capital inequality on income inequality in developing countries - Mahmood, Suraya; Mohd Noor, Zaleha; Law, Siong Hook (2012)
This paper examines the effect of human capital inequality on income inequality in Developing Countries using Gini coefficient as a consistent measurement for both of inequality. This study also adds a few control variables such as Globalization Index, GDP per capita and total of population using dynamic panel data Generalized method of Moment (GMM) for 55 countries over the period of 1970-2010. The empirical results show that, human capital inequality is significant with income inequality. However, other control variables are insignificant with income inequality except GDP per capita. Thus, to reduce income inequality and to give citizens equal opportunities, governments of developing countries and policymakers need to pay attention to human capital inequality.